258 RISING TO THE CHALLENGE: ORTHOGERIATRIC SERVICE IMPROVEMENT AND COVID-19. (25th October 2022) - Stankard, A; Thomas, N; Cosgrave, N; Conlon, B; Monaghan, P; Halpin, T; English, D; Byrne, P; McShane, S; Sohail, I; Grogan, AM; Reilly, A; et al.
Abstract: Background: Nationally agreed hip fracture standards have contributed to the improvement of outcomes in hip fracture patients. In 2020, our hospital was awarded "The Golden Hip" for achieving highest compliance with Irish Hip Fracture Standards (IHFS) nationally for 2019. Methods: Data from the Irish Hip Fracture Database (IHFD)was retrospectively analysed to assess our performance in 2020 versus 2019 in hip fracture patients over sixty. Multiple quality improvement interventions were put in place throughout 2019 to ensure improvement in IHFS1-6 compliance: Creation of the Hip Fracture Pathway Subgroup, IHFS 1 Breaches Audit, Orthogeriatric input at Orthopaedic inductions, weekly Multi-disciplinary Team meetings, a Nutritional Hip Fracture Pathway and addition of the Fracture Liaison Service Advanced Nurse Practitioner. Results: There were 239 hip fracture patients in 2020 vs 249 in 2019. IHFS1 compliance improved with the percentage of patients admitted to the Orthopaedic ward within 4 hours increasing to 71% in 2020 from 56% in 2019. There was improvement in IHFS2-time to surgery <48 hours- 66% in 2020 vs 60% in 2019. IHFS3-pressure ulcer rate-was at the national average, 3% in 2020 vs 2% in 2019. IHFS4 (reviewed by a Geriatrician), IHFS5 (received a bone health assessment) and IHFS6 (received a specialised falls assessment) were lower overall; 87% in 2020 vs 98% in 2019. For all quarters (Q), 43% of patients met all IHFS in our hospital in 2020 vs 32% in 2019, resulting in €90, 000 in Best Practice Tariff funding. Conclusion: Lower results for IHFS 4, 5 and 6 reflect the arrival of the COVID-19 pandemic which led to redeployment of the Orthogeriatric Service and redeployment of the MDT from end of Q1 to Q3. When services in 2020 were preserved, 1 in 2 hip fracture patients met all IHFS, vs 1 in 3 patients in 2019. Despite the pandemic, we continued to achieve the highest level of IHFS compliance nationally, being awarded a second consecutive "Golden Hip" for 2020.